Developing Reading Material Based on Local Culture at SMP Negeri 32 Medan - Dwi Putri, Ade Lestari; Azhary Tambusai (PT Inovasi Pratama Internasional, 2025)
Integrating local culture into the process of learning a foreign language has only recently begun to draw attention. Therefore, local culture-based English reading materials are a solution to attract students' interest in reading English. The objectives of this research are to develop the students’ English reading materials based on local culture at SMPN 32 Medan, to find out the validation of English reading material based on local culture at SMPN 32 Medan, and to explain the effectiveness of English reading material based on local culture at SMPN 32 Medan. This research adapted the R&D model proposed by Sugiyono (2013) with some modifications. The data was taken from students and teachers of SMPN 32 Medan and also expert judgment from Universitas Muslim Nusantara Al Washliyah Medan. The instruments of this research are questionnaire, documentation and test. The result of validation from the material expert judgment is 91.66% and the material expert judgment is 85.71%. It means that the product in very high category. The result of validation from the teacher is also high category, 88.63% . In addition, the product was also tested on students and the results showed a significant increase in scores after the students learned using the local culture-based reading materials. Unit 1 increased up to 10.36%, Unit 2 increased up to 12.15%, Unit 3 increased up to 14.06% and Unit 4 increased up to 15.26%. The average score of students, which was previously the highest at 78, increased to 89. The conclusion based on the research results shows that these English reading materials can be adopted as teaching materials as additional learning for English lessons that are interesting, contextual, and adapted to the Merdeka curriculum.